2008
DOI: 10.4049/jimmunol.181.9.6406
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Inhibit HIV-1 Gp120-Mediated Insults in Brain Microvascular Endothelial Cells

Abstract: HIV-1 infection has significant effect on the immune system as well as on the nervous system. Breakdown of the blood-brain barrier (BBB) is frequently observed in patients with HIV-associated dementia (HAD) despite lack of productive infection of human brain microvascular endothelial cells (HBMEC). Cellular products and viral proteins secreted by HIV-1 infected cells, such as the HIV-1 Gp120 envelope glycoprotein, play important roles in BBB impairment and HIV-associated dementia development. HBMEC are a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 49 publications
(87 reference statements)
5
57
0
Order By: Relevance
“…HIV-1 infection in this compartment is associated with progressive neurological impairments, including changes in cognitive and motor function and behavior (Lu et al, 2008). The degree of neurological impairment in HIV-associated dementia (HAD) and encephalitis does not correlate with viral load in the CNS but rather with the degree of monocyte infiltration and microglial activation (Glass et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 infection in this compartment is associated with progressive neurological impairments, including changes in cognitive and motor function and behavior (Lu et al, 2008). The degree of neurological impairment in HIV-associated dementia (HAD) and encephalitis does not correlate with viral load in the CNS but rather with the degree of monocyte infiltration and microglial activation (Glass et al, 1993).…”
mentioning
confidence: 99%
“…Recent reports indicate that cannabinoids inhibit viral expression and downregulate CC chemokine receptor 5 (CCR5), a chemokine receptor that is a coreceptor for HIV-1 entry (Rock et al, 2007). In addition, cannabinoid receptor agonists have been reported to decrease significantly the permeability of human brain microvascular endothelial cells induced by Gp120 by preventing the down-regulation of integral tight junction proteins (Lu et al, 2008). Given the importance of macrophage infiltration into the CNS in the pathology of HIV infection and that cannabinoids have been shown to have anti-inflammatory properties (reviewed in Cabral and Staab, 2005) that include inhibition of macrophage migration (Raborn et al, 2008), the effect of cannabinoids on macrophage migration to the HIV-1 protein Tat was evaluated.…”
mentioning
confidence: 99%
“…3), indicating the importance of this receptor in modulating neurotransmission (137). In the CNS, the expression of CB1 receptors was also demonstrated in astrocytes, microglial cells, pial vessels, cerebral microvascular smooth muscle cells, human brain endothelium, and pericytes (37,78,81,131,222,259) (Fig. 3).…”
Section: Biosynthesis and Receptors Of Endocannabinoids In Cells Invomentioning
confidence: 84%
“…Activated microglial cells from mice exhibit the highest CB2 receptor density on the leading edges (the front of migrating polarized cells), which may mediate their migration toward the source of endocannabinoid release, i.e., damaged neurons (247). Cerebrovascular endothelial cells express CB2 receptors together with CB1 and TRPV1 receptors, and these receptors are functional and possibly cooperative (81,131). Zhang et al (259) reported CB2 receptor expression in endothelial and smooth muscle cells of cerebral blood vessels, pericytes, astrocytes, and microglia.…”
Section: Biosynthesis and Receptors Of Endocannabinoids In Cells Invomentioning
confidence: 99%
“…More complex models involve monolayers of endothelial cells cultured above astrocytes, either on top of a collagen matrix (Biegel andPachter, 1994, Biegel et al, 1995) or on opposite sides of a membrane (Lu et al, 2008, Persidsky et al, 1997, Eugenin et al, 2006. The coculture allows tight junction formation to occur.…”
Section: 5d Model Of Bbb In Vitromentioning
confidence: 99%